Application of As-built Data in Building Retrofit Decision Making Process. (2015) - Wang, Chao; Cho, Yong K.
Abstract: With the growing needs of improving building sustainability, an increasing number of existing buildings need renovation to meet the expectation of the stakeholders. In the pre-design phase, it is very critical to have the best decision made to satisfy both the project budget and the performance standard. For a new buildings, a whole building energy simulation analysis is very helpful for this decision making process because it can provide the stakeholders the evaluation results of all alternative solutions. However, for existing buildings, the as-built data required for the building energy modeling process is not always available, and its manual collection process is time-consuming and error prone. This paper first reviews the state-of-the-art methods of automated data collection, and then introduces the automatic as-built BIM model creation process through a case study. This study also successfully demonstrated the interoperability between the created as-built model and a typical energy simulation tool. At last, a discussion is made about the limitations and challenges of the current state of practice to enlighten the future direction.